2016
DOI: 10.1186/s12893-016-0198-2
|View full text |Cite
|
Sign up to set email alerts
|

The enigma of primary and secondary encapsulating peritoneal sclerosis

Abstract: BackgroundEncapsulating Peritoneal Sclerosis (EPS) describes a variety of diseases that are frequently confused with different names and different etiopathogeneses. The aim of this article is to report personal experience of focusing on correct classification and the status of current diagnosis and treatment.MethodsA retrospective analysis was performed. Age, sex, ethnic origin, past medical history, symptoms and their duration, radiological tools and signs, laboratory tests, preoperative diagnosis, surgical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 35 publications
0
45
0
2
Order By: Relevance
“…Two variants are usually seen, primary and acquired (secondary). 9 Primary are seen in adolescent girls in tropical and subtropical countries. It is attributed to retrograde menstruation.…”
Section: Classificationmentioning
confidence: 99%
“…Two variants are usually seen, primary and acquired (secondary). 9 Primary are seen in adolescent girls in tropical and subtropical countries. It is attributed to retrograde menstruation.…”
Section: Classificationmentioning
confidence: 99%
“…The basis of any surgery is the removal of the membrane and division of any adhesions. Various procedures described in the literature include resection of the peritoneum and fibrous tissue and separation of adhesions to release the bowel, partial membrane excision with adhesiolysis, resection and anastomosis, resection and anastomosis with protective stoma, depending on patient-related factors (3,14). However, Wang et al (10) have found surgery not very helpful in patients with cocoon secondary to carcinoma in their study.…”
Section: Discussionmentioning
confidence: 97%
“…Contrast-enhanced computed tomography (CECT) is the most helpful radiological tool for confirming the diagnosis, planning therapy, and avoiding unnecessary resection in patients with SEP (11). Characteristic CT finding helpful in clinching the diagnosis is conglomeration of contrast dense small bowel loops in the centre encased by contrast free capsule in the periphery (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most common in adolescent girls. 1 Common causes like idiopathic, peritoneal dialysis related, malignancy (NET, dermoids), drugs like β blockers, ergot, generalized peritonitis. 2,3 According to BoWei classification, its divided into 3 types, 3 types according to extent of encasing membrane: Type I membrane encapsulates small intestine partially.…”
Section: Introductionmentioning
confidence: 99%